Natural Killer cells demonstrate distinct eQTL and transcriptome-wide disease associations, highlighting their role in autoimmunity - James J. Gilchrist; Seiko Makino; Vivek Naranbhai; Piyush K. Sharma; Surya Koturan; Orion Tong; Chelsea A. Taylor; Robert A. Watson; Alba Verge de los Aires; Rosalin Cooper; Evelyn Lau; Sara Danielli; et al. (Nature Communications, 2022)
Natural Killer cells are key mediators of anti-tumour immunosurveillance and anti-viral immunity. Here, the authors map regulatory genetic variation in primary Natural Killer cells, providing new insights into their role in human health and disease.